Population Immunity to Measles in the Republic of Belarus Following Long-Standing Vaccination - E. О. Samoilovich; G. V. Semeiko; M. A. Yermalovich; I. N. Glinskaya; V. S. Vysotskaya (Эпидемиология и вакцинопрофилактика)
Relevance. Despite the progress made in eliminating measles and rubella in the European Region, the measles situation has now worsened - four countries in the region have lost their status of eliminating measles.Aims - to assess population immunity to measles in the Republic of Belarus, to determine its age and regional characteristics for identification of groups of higher risk of infection.Results. The results of evaluation of IgG antibodies to measles under the conditions of a long-term (since 1967 - singledose immunization schedule, since 1987 - two-dose) vaccination, carried out in 2019, in 2229 residents of the Republic of Belarus 2-75 years of age are presented. Antibodies were detected using Serion ELISA classic Measles Virus IgG, Virion\Serion, Germany. Antibodies concentration 150 mIU/ml or more was considered as evidence of protection against measles. It was found that the level of seroprevalence against measles in the Republic of Belarus is 84.6%, that is slightly lower than the threshold level (90-95%) sufficient to prevent wide transmission of the virus in case of its importation. Level of seroprevalence was the highest in children 2-5 years old (96.9%) and in adults 46 years of age and older (93.0% or more) and did not reach 90% in all other age groups. The most susceptible to measles were adults 31-40 years old (born 1979-1988) - antibodies in protective concentrations were detected in less than 80% of them (31-35 years old - 78.9% and 36-40 years old - 78,4%). The mean antibody concentration in seropositive individuals also varied in age groups. A high concentration of antibodies (more than 1000 mIU/ml) was observed in children 2-5 years old, as well as in adults over 40 years old. Among the latter, the concentration of antibodies increased with age: 41-45 years old - 1069 mIU/ ml, 46-55 years old -1212 mIU/ml, 56-65years old -1582 mIU/ml, 66-75 -1849 mIU/ml. Among people 6-35 years old it was 500600 mIU/ml and was slightly higher among persons 36-40 years old (781 mIU/ml).Conclusions. For further control of infection, along with maintaining a high (97% or more) level of routine immunization, it is necessary to ensure mopping up immunization of unvaccinated individuals and those without immunization data.